Characterization of Axial Forces to the Head During Kipping Handstand Push-ups - Geoffrey M Bove (Journal of Coaching and Sports Science, 2025)
Background: Thousands of athletes perform kipping handstand push-ups (kHSPUs). The safety of kHSPUs has been questioned because of vertical impacts upon the head, but no previous study has examined the ground reaction forces sustained during these exercises.Aims: This exploratory, observational cross-sectional study measured the forces exerted on the head and supported by the neck during kipping handstand push-ups (kHSPU). The goal was to compare these forces with known thresholds that can damage the cervical spine. The researcher also aimed to determine how often people experience symptoms after performing these exercises.Methods: Sixteen volunteers performed three sets of up to 7 kHSPUs with their head and one hand contacting force platforms. Force and video recordings were made while performing the exercises. Volunteers were asked if they had neck pain or headaches related to the exercises.Result: Force profiles showed distinct landing and kipping peaks. Landing forces were higher than during a headstand but less than body weight. Forces were greatest during the "kip" and usually exceeded body weight. Participants who reported pain following kHSPUs extended their necks during the exercises. Forces to the head during kHSPUs were below forces proposed for damage to the young male cervical spine but overlapped those proposed for damage to female cervical spines.Conclusion: While kipping handstand push-ups may be safe for young and previously uninjured male athletes, they may be unsafe for females and those with previous injuries or other compromising factors. Detailed inquiry about symptoms and neck injuries secondary to these exercises is warranted. Based on the initial observations, until these exercises are shown to be safe, athletes should be informed about these possible risks before performing the exercises.